Waste management within the scope of environmental public awareness based on cross-sectional survey and social interviews - Zhou, Yang; İnce, Fatma; Teng, Haikun; Kaabar, Mohammed K. A.; Xu, Jiajun; Yue, Xiao-Guang (Frontiers in Environmental Science, 2022)
Since the natural resources of the world are not unlimited, the effective use of resources and the access of future generations to these resources concern all societies on a global scale. From this point of view, waste management strategies should be examined in terms of medical, household, and other waste types. Thereby, this study aims to examine the level of public awareness in waste management by studying the perception, perspective, practice about waste’s aspects. The survey in this study mentions questions on waste management knowledge, public awareness, and behaviors among social interviews of pharmacy students receiving laboratory training in the field of health. Internal consistency reliability is used to verify the uniformity of questions in this study. Pearson correlation, t-test, and the analysis of variance (ANOVA) are performed to study the differences between groups.The results of the data analysis show that public awareness and waste management knowledge, public awareness, and behaviors have a significant positive correlation, which provides us with a good basis for designing environmental strategies.The first module’s outcomes of the questionnaire reveal a high degree of waste management among students. On the contrary, woman participants demonstrate a higher public awareness and application of the environment. Furthermore, there are significant correlations between the other modules and demographic factors with family education. According to the results, the public awareness of the participants who were members of an environmental organization is different from others. Finally, the participants state that the problem of not managing wastes effectively causes the most damage to the soil and all other natural resources after water.